Thermal-hydraulic analysis of a 7-pin sodium-cooled fast reactor wire-wrapped fuel bundle. (October 2020) - Wang, Dianle; Peng, Changhong; Guo, Yun
Highlights: The sensitivity analysis of geometric simplification was conducted. The results show that geometric simplification has great influence on friction factor and should be taken into consideration seriously. The sensitivity analyses of Reynolds-Averaged Navier-Stokes (RANS) model were conducted. Strong secondary flows and eddies were observed. Local heat transfer was analyzed. The inhomogeneity of heat transfer is considerable. Kays model which is one of the local turbulent Prandtl number models was adopted. The default value 0.85 of turbulent Prandtl number would overestimate the heat transfer performance. The results of Kays model agree well to experiment correlation. Abstract: The thermal-hydraulic characteristics of 7-pin sodium-cooled fast reactor (SFR) wire-wrapped fuel bundle were numerically investigated by commercial computational fluid dynamics (CFD) code ANSYS Fluent. The sensitivity analyses of mesh size, geometric simplification and Reynolds-Averaged Navier–Stokes (RANS) model were conducted. The turbulent Prandtl number model was adopted. The flow field and heat transfer were analyzed. The results show that the geometric simplification has great influences on friction factor and Nusselt number. The simplification should be taken into consideration seriously. The results of the standard k-ε model, realizable k-ε model and Reynolds stress model (RSM) model are close. The results of the Shear Stress Transport (SST) k-ω model has the maximum error compared with experiment correlation. The strong secondary flows and eddies were observed. The flow velocity near the contact of wire and rod is low and causes high temperature. At the cross section of z =50mm, the difference between the highest and lowest temperatures of the central rod is 13K, and the highest and lowest local Nusselt Numbers are 2.29 and 4.07 respectively, which indicates that the inhomogeneity of heat transfer is considerable. The velocity distribution of the boundary layer agrees well with the law-of-the-wall while the temperature boundary layer is much thicker than that of velocity. At least at y + <100, heat transfer is dominated by molecular heat conduction. At high Peclet number, the default value 0.85 of turbulent Prandtl number overestimates the heat transfer performance and the results of Kays model are closer to the experiment correlation. At very low Peclet number, Kays model has a quite different from experiment correlation. This study provides a reference for SFR design.